Molecular Screening of Extended Spectrum β-lactamases in Klebsiella pneumoniae isolated from Clinical Sources (Journal of Pharmaceutical Negative Results, 2022)
Klebsiella pneumoniae is a major pathogen responsiple for nosocomial infections in world hospitals . One of the causes for the drug resistance in the Klebsiella pneumoniae is the production of ESBls enzymes.This research documented TEM , SHV , and CTX-M for the first time among Klebsiella pneumoniae in Al-Anbar hospitals of Iraqi. All studied clinical isolates of K. pneumoniae (30) resistant- beta lactam from 100 isolates were collected from different clinicals sources such as (burned, wounds, sputum,and urine samples). The susceptibility to different antibiotics was tested by VITEK-2 system. The bla TEM , SHV , and CTX-M genes were detected by conventional PCR and the result showed 30/30 (100%) strains harbored these genes. This results showed the coexistence of these genes in one strains of K. pneumoniae, while indicated widespread ESBLs in Anbar, Iraq.